2021
DOI: 10.3390/plants10010123
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Photo-Induced Cytotoxic Activity of Cachrys sicula and Cachrys libanotis Enriched-Coumarin Extracts against Human Melanoma Cells

Abstract: Photochemotherapy is one of the most interesting current therapeutic approaches for the treatment of melanoma. Different classes of naturally occurring phytochemicals demonstrated interesting photoactive properties. The aim of this study was to evaluate the photocytotoxic potential of two Cachrys species from Southern Italy: C. sicula and C. libanotis (Apiaceae). The enriched-coumarin extracts were obtained from aerial parts through both traditional maceration and pressurized cyclic solid-liquid (PCSL) extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Among all melanoma cells available for research, the C32 human cell line was chosen due to being amelanotic, thus not interfering with the illumination settings of the study. Moreover, they have been previously combined with photosensitizers [ 41 , 42 ] and used for toxicological screenings of plant compounds [ 43 , 44 , 45 , 46 ]. Finally, due the feasibility of further illumination and administration of microalgae in prospective patients, melanomas represent a good candidate for the translation of this concept into clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Among all melanoma cells available for research, the C32 human cell line was chosen due to being amelanotic, thus not interfering with the illumination settings of the study. Moreover, they have been previously combined with photosensitizers [ 41 , 42 ] and used for toxicological screenings of plant compounds [ 43 , 44 , 45 , 46 ]. Finally, due the feasibility of further illumination and administration of microalgae in prospective patients, melanomas represent a good candidate for the translation of this concept into clinics.…”
Section: Discussionmentioning
confidence: 99%
“…(n = 3). 3 Marrelli et al, 2021 [11]. Results are expressed as mg of chlorogenic acid (for phenolics) and mg of quercetin (for flavonoids) per g of dry plant material.…”
Section: Phytochemical Profilementioning
confidence: 99%
“…The name C. ferulacea is a synonymous of Prangos ferulacea Lindl., being the Cachrys group divided into a number of genera including not only Cachrys and Prangos , but also Alocacarpum , Azilia , Bilacunaria , Diplotaenia , Eriocycla and Ferulago [ 10 ]. The major secondary metabolites of these species were identified in coumarins and furanocoumarins, among which bergapten represents one of the most interesting molecules [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, screening for natural anti‐cancer drugs has become an essential tool in the treatment and prevention of cancer (Lu et al, 2021). More and more studies have shown that XAT has great potential in treating cancer, and according to incomplete statistics, XAT can inhibit a range of diseases such as colon cancer (Bartnik, Slawinska‐Brych, Zurek, Kandefer‐Szerszen, & Zdzisinska, 2017), Hepatocellular carcinoma (HCC) (El‐Nakkady, Roaiah, El‐Serwy, Bassyouni, & Soliman, 2015; Palacharla et al, 2019), skin cancer (Marrelli et al, 2021), T‐cell lymphoma (Cunderlikova et al, 2014), prostate cancer, and glioma (Lu et al, 2017). The anti‐cancer mechanism of XAT mainly includes two aspects, one is the induction of apoptosis and the other is the inhibition of disorderly cell proliferation.…”
Section: Pharmacological Effects Of Xanthotoxinmentioning
confidence: 99%